2012
DOI: 10.1016/j.juro.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Followup of Neutrophil-to-Lymphocyte Ratio and Recurrence of Clear Cell Renal Cell Carcinoma

Abstract: The posttreatment neutrophil-to-lymphocyte ratio change was a significant prognostic factor for recurrence as well as tumor size and pathological tumor stage in patients with clear cell renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 24 publications
5
89
0
Order By: Relevance
“…However, in an AS-eligible cohort, in which the variability of PSA is limited, leukocyte subgroups and NLR analysis might potentially offer additional parameters that can further stratify a seemingly homogenous group of patients. Although studies have also shown that the postoperative NLR is a prognostic marker for recurrence and measure of response to therapy in renal cell carcinoma, 26,27 our analyses for this project were limited to the preoperative setting to assess the cancer-related inflammation manifested in the pretreatment hematologic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, in an AS-eligible cohort, in which the variability of PSA is limited, leukocyte subgroups and NLR analysis might potentially offer additional parameters that can further stratify a seemingly homogenous group of patients. Although studies have also shown that the postoperative NLR is a prognostic marker for recurrence and measure of response to therapy in renal cell carcinoma, 26,27 our analyses for this project were limited to the preoperative setting to assess the cancer-related inflammation manifested in the pretreatment hematologic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Preoperative anemia (hemoglobin <13.5 g/dL in males and <12.0 g/dL in females) is established adverse prognostic factor, while recent studies confirm that pre- and post-treatment neutrophil to lymphocyte ratio is a significant prognostic factor for recurrence in patients with clear cell carcinoma. [2122]…”
Section: Discussionmentioning
confidence: 99%
“…[ 153,431] Localized renal cell carcinoma The presence of intratumoral neutrophils was associated with short recurrence-free survival. [390] Metastatic renal cell carcinoma Patients with elevated neutrophil count (>6,500 cells/μl) showed a shorter overall survival.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%